ALX4 gain-of-function mutations in non-syndromic craniosynostosis - Yagnik, Garima (2012)
Craniosynostosis is the early fusion of one or more sutures of the infant skull and is a common defect occurring in approximately 1 of every 2,500 live births. Non-syndromic craniosynostosis accounts for approximately 80% of all cases and is thought to have strong genetic determinants that are yet to be identified. ALX4 is a homeodomain transcription factor with known involvement in osteoblast regulation. By direct sequencing of the ALX4 coding region in sagittal or sagittal-suture-involved non-syndromic craniosynostosis probands, we identified novel, nonsynonymous, familial variants in three of 203 individuals with NSC. Using dual-luciferase assay we show that two of these variants (V7F and K211E) confer a significant gain-of-function effect on ALX4. Our results suggest that ALX4 variants may have an impact on the genetic etiology of NSC.